2018
DOI: 10.3389/fimmu.2018.01208
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sex Stratification in Autoimmune Disease Biomarker Research: A Systematic Review

Abstract: The immune system is highly dynamic and regulated by many baseline characteristic factors. As such, significant variability may exist among different patient groups suffering from the same autoimmune disease (AD). However, contemporary research practices tend to take the reductionist aggregate approach: they do not segment AD patients before embarking on biomarker discovery. This approach has been productive: many novel AD biomarkers have recently been discovered. Yet, subsequent validation studies of these bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 216 publications
1
17
1
Order By: Relevance
“…Gender exerts an effect on the prevalence as well as the clinical phenotype and outcome in SLE . Male patients with SLE tended to have higher mortality than their female counterparts in previous studies, which was also found in our cohort (Table ). Nevertheless, contradictory results have been reported .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Gender exerts an effect on the prevalence as well as the clinical phenotype and outcome in SLE . Male patients with SLE tended to have higher mortality than their female counterparts in previous studies, which was also found in our cohort (Table ). Nevertheless, contradictory results have been reported .…”
Section: Discussionsupporting
confidence: 86%
“…Because of the overall low number of deaths in previous studies and our study, larger prospective studies are warranted to conclusively determine whether male gender is associated with increased mortality in SLE. In addition, previous studies reported that men with SLE showed serositis, renal diseases, and cardiovascular complications more frequently, but less frequently with arthritis and photosensitivity compared with their female counterparts . However, except for arthritis, these findings were not observed in our data, and this may be due to the small number of male patients in our cohort (Table ).…”
Section: Discussioncontrasting
confidence: 81%
“…In the Latvian population, rs9275596 rare allele (C) was identified as a risk factor in the MS common cohort (p < 0.001) and appears to be disease-susceptible in the female group (p < 0.01, Figure 4). Sex-specific differences in incidence, prevalence, and severity are well-known features of autoimmune disease epidemiology [36], including MS [2]. Stratification of the MS cohort in the Latvian population by sex revealed significant differences in alleles (p < 0.01, multiplicative model) and genotypes frequency (p < 0.001, recessive model; Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…This was not observed in wild-type mice or in response to individual p110a or p110d deletion in the same cohort. It is interesting to note that females were more susceptible than male mice as this is often the case in human autoimmune disorders and indicate that the mechanisms underlying this phenotype could be relevant to human disease (56). Spontaneous peripheral neuropathy has been described in females aged 99-100 wk from several mouse strains, including C57BL/6 mice (57).…”
Section: Discussionmentioning
confidence: 99%